2021
DOI: 10.1093/eep/dvab004
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal DEHP exposure induces sex- and tissue-specific DNA methylation changes in both juvenile and adult mice

Abstract: Di(2-ethylhexyl) phthalate (DEHP) is a type of phthalate plasticizer found in a variety of consumer products and poses a public health concern due to its metabolic and endocrine disruption activities. Dysregulation of epigenetic modifications, including DNA methylation, has been shown to be an important mechanism for the pathogenic effects of prenatal exposures, including phthalates. In this study, we used an established mouse model to study the effect of perinatal DEHP exposure on the DNA methylation profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…Our recent work in TaRGET II demonstrates that changes in DNA methylation after perinatal exposure to lead or the plasticizer di-2-ethylhexyl phthalate are highly tissue-and sexdependent, with little concordance between liver and blood. 156,184,281 Our findings are in keeping with recent work in human subjects, which found correlation in DNA methylation between blood and the liver at only a minority of CpG sites within 35 hemostatic genes. 282 Additional studies have demonstrated limited correlation in DNA methylation between human blood and other tissues.…”
Section: Challenges To the Field Of Toxicoepigeneticssupporting
confidence: 90%
See 2 more Smart Citations
“…Our recent work in TaRGET II demonstrates that changes in DNA methylation after perinatal exposure to lead or the plasticizer di-2-ethylhexyl phthalate are highly tissue-and sexdependent, with little concordance between liver and blood. 156,184,281 Our findings are in keeping with recent work in human subjects, which found correlation in DNA methylation between blood and the liver at only a minority of CpG sites within 35 hemostatic genes. 282 Additional studies have demonstrated limited correlation in DNA methylation between human blood and other tissues.…”
Section: Challenges To the Field Of Toxicoepigeneticssupporting
confidence: 90%
“…Indeed, as chemical exposures may cause precocious aging of the epigenome, a single cross-sectional study of adult tissues may miss important exposure-related changes . Moreover, biomarkers of environmental exposures and disease may differ based on age …”
Section: Challenges and Opportunities In Toxicoepigeneticsmentioning
confidence: 69%
See 1 more Smart Citation
“…The impact of DEHP exposure on reproduction and social behavior is not only transgenerational but also dose-specific in both males and females [ 79 ]. In addition, the perinatal exposure of both juvenile and adult mice to DEHP induces sex- and tissue-specific DNA methylation alterations [ 80 ]. DEHP exposure during gestation increased DNMT3a and DNMT3b ( Figure 3 ) expression in adult rat testes of F1 and in offspring, suggesting that epimutations may be a potential mechanism of DEHP-mediated testicular toxicity [ 81 ].…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
“…Several studies suggest that prenatal exposure to DEHP might induce developmental toxicity and endocrine disruption by altering DNA methylation in several tissues, such as the liver, blood cells, heart, and brain [ 55 , 56 , 57 ]. However, few studies have reported the epigenetic modification of prenatal DEHP exposure on the hypothalamic Oxtr gene.…”
Section: Discussionmentioning
confidence: 99%